Quantitative Trait Loci and Maternal Effects Affecting the Strong Grain Dormancy of Wild Barley (Hordeum vulgare ssp. spontaneum) - Nakamura, Shingo; Pourkheirandish, Mohammad; Morishige, Hiromi; Sameri, Mohammad; Sato, Kazuhiro; Komatsuda, Takao (Frontiers in Plant Science, 2017)
Wild barley (Hordeum vulgare ssp. spontaneum) has strong grain dormancy, a trait that may enhance its survival in non-cultivated environments; by contrast, cultivated barley (Hordeum vulgare ssp. vulgare) has weaker dormancy, allowing uniform germination in cultivation. Malting barley cultivars have been bred for especially weak dormancy to optimize their use in malt production. Here, we analyzed the genetic mechanism of this difference in seed dormancy, using recombinant inbred lines (RILs) derived from a cross between the wild barley accession ‘H602’ and the malting barley cultivar ‘Kanto Nakate Gold (KNG)’. Grains of H602 and KNG harvested at physiological maturity and dried at 30°C for seven days had germination of approximately 0% and 100%, respectively. Analysis of quantitative trait loci (QTL) affecting grain dormancy identified the well-known major dormancy QTL SD1 and SD2 (located near the centromeric region and at the distal end of the long arm of chromosome 5H, respectively), and QTL at the end of the long arm of chromosome 4H and in the middle of the long arm of chromosome 5H. We designated these four QTL Qsd1-OK, Qsd2-OK, Qsdw-4H, and Qsdw-5H, and they explained approximately 6, 38, 3, and 13% of the total phenotypic variation, respectively. RILs carrying H602 alleles showed increased dormancy levels for all QTL. The QTL acted additively and did not show epistasis or QTL–environment interactions. Comparison of QTL locations indicated that all QTL except Qsdw-5H are likely the same as the QTL previously detected in the doubled haploid population from a cross between the malting cultivar ‘Haruna Nijo’ and ‘H602’. We further examined Qsd2-OK and Qsdw-5H by analyzing the segregation of phenotypes and genotypes of F2 progenies derived from crosses between RILs carrying specific segments of chromosome 5H from H602 in the KNG background. This analysis confirmed that the two genomic regions corresponding to these QTL are involved in the regulation of grain dormancy. Germination tests of F1 grains derived from reciprocal crosses between H602 and KNG revealed that the H602 strong dormancy phenotype shows maternal inheritance with incomplete dominance. These results provide new insight into the mechanisms regulating grain dormancy in barley.